Succession Planning for Leadership Transformation for South African Non-Profit Organisations - Buchholz, Este (Graduate School of Business (GSB), 2025)
Non-profit organisations (NPOs) play a vital role in South African society, providing critical services for many underserved and marginalised communities. Despite the evidence of the importance of NPOs in transforming the South African economy and society, there is very little research on succession planning for executive leadership transformation within this sector. The Literature on this topic is primarily based on case studies from other countries. South African studies were conducted in the public or private sector, which does not address the unique context of NPOs. This dissertation aims to address the gap in the current academic literature by exploring the unique ways in which NPOs implement succession planning to achieve successful internal executive leadership transformation within the South African non-profit sector. The primary research question is, “How do NPOs plan organisational succession to achieve successful internal executive leadership transformation?” The study used Eisenhardt's method of building theories from case study research as the overarching research methodology. Data was collected from eight NPOs. Semi-structured interviews were conducted with the ex-Executive Director (ED) and the incumbent ED of each NPO. Both in-case and cross-case analyses were used to derive the findings. Key findings from the research include the importance of being intentional about creating diverse and inclusive organisations, having reciprocal trust between the Executive Director and the board, and creating informal learning opportunities for potential successors. Future research should focus on the first 12 - 24 months of the incumbent ED, exploring the main challenges faced by the new leader as a black person.